1998
DOI: 10.1093/humrep/13.6.1686
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) in endometriosis

Abstract: Angiogenesis is likely to be involved in the pathogenesis of endometriosis. According to the transplantation theory, when the exfoliated endometrium is attached to the peritoneal layer, the establishment of a new blood supply is essential for the survival of the endometrial implant and development of endometriosis. From the known angiogenic factors, vascular endothelial growth factor (VEGF) has emerged as a pivotally important regulator of normal angiogenesis and pathological neovascularization. The VEGF prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
281
3
22

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(326 citation statements)
references
References 22 publications
20
281
3
22
Order By: Relevance
“…VEGF-A seems to be one of the most important angiogenic growth factors in the regulation of angiogenesis in general and probably also in both eutopic and ectopic endometrium (Li et al 1994, McLaren et al 1996b, Shifren et al 1996, Torry et al 1996, Donnez et al 1998, Mö ller et al 2001. We can show that VEGF-A and its receptors VEGFR-1 and VEGFR-2 are present in both eutopic and ectopic endometrium, and their relation to microvessel density and proliferative activity will be discussed later.…”
Section: Angiogenic Activity In Endometriotic Lesionssupporting
confidence: 50%
See 1 more Smart Citation
“…VEGF-A seems to be one of the most important angiogenic growth factors in the regulation of angiogenesis in general and probably also in both eutopic and ectopic endometrium (Li et al 1994, McLaren et al 1996b, Shifren et al 1996, Torry et al 1996, Donnez et al 1998, Mö ller et al 2001. We can show that VEGF-A and its receptors VEGFR-1 and VEGFR-2 are present in both eutopic and ectopic endometrium, and their relation to microvessel density and proliferative activity will be discussed later.…”
Section: Angiogenic Activity In Endometriotic Lesionssupporting
confidence: 50%
“…This includes aromatase activity in the eutopic endometrium from women with moderate to severe endometriosis, but not in those of disease-free women (Noble et al 1996). There is also a higher VEGF-A content in the secretory phase eutopic glandular epithelium (Donnez et al 1998) and an elevated endothelial cell proliferation in women with endometriosis (Wingfield et al 1995), compared with those without. Accumulated data thus suggest that eutopic endometrium of women with endometriosis behaves differently from the endometrium of women without the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous peritoneal blood vessels surround active endometriotic lesions, and the implant itself is also endowed with a rich vascularized area; this can be observed under histological examination (Nisolle et al 1993, Nap et al 2004 and confirms the essential role that angiogenesis plays in the development and continuation of endometriotic lesions (Shifren et al 1996, Donnez et al 1998, Becker et al 2005. In this regard, it has been observed that human endometrium engrafted in immunocompromised mice promotes the growth of neovessels from the surrounding host vascular network in order to provide the endometriotic lesions with an adequate blood supply.…”
Section: Introductionmentioning
confidence: 77%
“…Endometriosis has invasive characteristics as endometrial tissue must attach to and invade the peritoneum, establish a blood supply, and continue to proliferate to form an ectopic lesion. [12][13][14][15] Understanding lymphatic drainage is considered crucial in diagnosis, prognosis, and treatment of invasive diseases. Also, lymphatic spread is hypothesized to play a role in pathogenesis of endometriosis and is thought to account for displacement of endometrial cells at unusual locations, other than those that would otherwise be accessible to retrograde menstrual flow.…”
Section: Introductionmentioning
confidence: 99%